Synergizing the GASING Method and Quantum Learning: An Effort to Optimize Elementary School Students' Mathematical Problem-Solving Abilities - Rabudin Rabudin; Yeni Yuniarti; Dede Trie Kurniawan; Marcia Ann Surya (FKIP Universitas Lampung, 2026)
The mathematical problem-solving abilities of elementary school students are still relatively low; this is caused by the high cognitive load they have to face when learning new complex materials and the lack of mental readiness to learn. This study aims to evaluate the effectiveness of the synergy between the GASING (Easy, Fun, Enjoyable) method and the Quantum Learning approach in improving elementary school students' mathematical problem-solving abilities. This study used a quantitative, quasi-experimental design (non-equivalent control group design) involving 140 3rd-grade elementary school participants in Singkawang City, with six schools selected through purposive sampling. The research instrument was a validated test item on mathematical problem-solving abilities. Data were obtained through pretest and posttest assessments, then analyzed quantitatively using Paired Sample T-Test and Quade's Rank Analysis of Covariance (ANCOVA) to address non-normally distributed residual data. The results of the study indicate that the experimental group experienced a significant increase in average scores, from 29.14 to 77.21 (p < 0.001). The results of the Quade's Rank ANCOVA test showed a significant difference between the two groups (F = 73.067, p < 0.001), with an effect size of 38.3% (R2 = 0.383) in the large category. Analysis of the learning trajectory using a scatter plot showed that all students experienced a steady increase in their skills, with no extreme outliers. This study concludes that the synergy of the GASING method and the Quantum Learning approach can reduce students' cognitive load through systematic deconstruction of material while creating a learning environment that supports their mental readiness. This framework provides an effective teaching method for educational practitioners to address mastery of classical mathematics competencies. Keywords: GASING method, quantum learning, problem-solving abilities, mathematical competence, elementary school.